An Intelligent and Service Based Smart Agriculture Recommendation System - Venu, Sivakumar; Kumar, R. G.; Kumar, Meriga Kiran; Prasad, TVS Gowtham; Suresh, Badugu; Neelima, P. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In Ancient India, people were depended on farming for their livelihood. Even today, Agriculture and allied sectors contributes one of the major portion in the Pi-chart of India’s GDP. But day by day, Agriculture sector declining and many are reluctant towards farming due to many reasons Such as Short of water levels in the underground, Lack of seasonal cropping, Multi cropping, Soil management etc. Artificial intelligence and machine learning is research area that can make use of to develop algorithms which will give assistance to the human in making right decisions by taking numerous in to account such a climatical conditions, Soil factors, idea on seasonal crops, right crops for multi cropping for better yield etc,. This paper presents several machine learning algorithms as a part of Agriculture Recommendation System in selecting right crop for right soil and climatical conditions to improve yield of the crop, to make farmer more flexible and comfort to farming with proper soil management.